2020
DOI: 10.3390/ijerph17072480
|View full text |Cite
|
Sign up to set email alerts
|

Economic Crisis and Sexually Transmitted Infections: A Comparison Between Native and Immigrant Populations in a Specialised Centre in Granada, Spain

Abstract: This study aimed to analyse the influence of the economic crisis on the prevalence of sexually transmitted infections (STIs) in the immigrant population compared to the native population. A cross-sectional study was conducted by reviewing 441 clinical records (329 Spanish nationals and 112 non-Spanish nationals) of individuals who, between 2000 and 2014, visited an STI clinic in Granada and tested positive for an infection. Descriptive statistical analyses were performed, and infection rates, odds ratios, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Furthermore, the current financial situation impacts on the incidence of STIs, mainly in the most vulnerable population [ 1 , 7 , 8 , 9 , 10 ]. In the recent economic crisis period (2008–2014) [ 11 , 12 , 13 , 14 ], syphilis and gonorrhoea reappeared in Spain, and the incidence of HIV, hepatitis, and HPV increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the current financial situation impacts on the incidence of STIs, mainly in the most vulnerable population [ 1 , 7 , 8 , 9 , 10 ]. In the recent economic crisis period (2008–2014) [ 11 , 12 , 13 , 14 ], syphilis and gonorrhoea reappeared in Spain, and the incidence of HIV, hepatitis, and HPV increased.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, today, despite the outstanding advance in medical knowledge and development of primary health care, sexual prevention programs seem to continue being inefficient, since the number of STIs continues to increase [ 1 ]. In this sense, an increase in STIs may be observed in Spain in general [ 19 ] and in the province of Granada in particular [ 10 , 15 ], which becomes an especially alarming issue.…”
Section: Introductionmentioning
confidence: 99%
“…Some migrants are exposed to sexual vulnerability due to their migration route, social isolation, administrative and housing insecurity, and homophobia discrimination (Cordel et al, 2022 ). Indeed, research carried out in Spain amply shows that the risk of having an STI is higher in the migrant population (Diaz et al, 2013 ; Pérez-Morente et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most relevant STIs, due to the absence of curative treatments and vaccines, is human immunodeficiency virus (HIV); the results of a study carried out in Spain with nursing students show that they have a positive attitude towards HIV patients, and this may improve their future healthcare practice in tackling this condition [ 2 ]. The identification of groups vulnerable to STIs has a special relevance for prevention programs; Perez-Morente et al have found that immigrant women in periods of crisis are more susceptible to acquiring an STI [ 3 , 4 ]. Screening and diagnostic methods, improved treatments, as well as the availability of more effective vaccines also deserve special attention.…”
mentioning
confidence: 99%